2017
DOI: 10.1080/03007995.2017.1383890
|View full text |Cite
|
Sign up to set email alerts
|

The importance of calprotectin levels in obstructive sleep apnea syndrome severity

Abstract: Calprotectin values were elevated in OSAS patients and it can be used as a marker of severe OSAS. Future studies can support our study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…It is known that increased levels of several inflammatory mediators play roles in obstructive sleep apnea syndrome (OSAS). Torun et al measured serum CLP levels in a small cohort of OSAS patients and found no significant difference in CLP between the OSAS and normal groups [193]. However, significantly increased CLP values were determined in severe OSAS patients when compared to the other OSAS groups [193].…”
Section: Clp In Obstructive Sleep Apnea Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…It is known that increased levels of several inflammatory mediators play roles in obstructive sleep apnea syndrome (OSAS). Torun et al measured serum CLP levels in a small cohort of OSAS patients and found no significant difference in CLP between the OSAS and normal groups [193]. However, significantly increased CLP values were determined in severe OSAS patients when compared to the other OSAS groups [193].…”
Section: Clp In Obstructive Sleep Apnea Syndromementioning
confidence: 99%
“…Torun et al measured serum CLP levels in a small cohort of OSAS patients and found no significant difference in CLP between the OSAS and normal groups [193]. However, significantly increased CLP values were determined in severe OSAS patients when compared to the other OSAS groups [193]. More recently, Kum et al confirmed that the serum CLP level could be used as an OSA severity indicator [194].…”
Section: Clp In Obstructive Sleep Apnea Syndromementioning
confidence: 99%
“…Calprotectin level is elevated in patients with moderate and severe obstructive sleep apnea [ 53 ]). Similarly, Torun’s study showed that it could be used as a marker for the severity of obstructive sleep apnea syndrome [ 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%